2011
DOI: 10.3109/13813455.2011.560950
|View full text |Cite
|
Sign up to set email alerts
|

The adipokine zinc-α2-glycoprotein activates AMP kinase in human primary skeletal muscle cells

Abstract: These results show that ZAG leads to phosphorylation of AMPKα and ACC, thereby activating a pathway central to the regulation of energy metabolism. This mechanism may be involved in mediating the effects of ZAG in relation to increased energy utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…However, ZAG did not display the thermogenic effects of the b-adrenoceptor agonist, nor did it increase b 3 -adrenoceptor or UCP1 (uncoupling protein 1) gene expression in brown adipose tissue, thereby implying that it does not behave as a typical b 3/2 -adrenoceptor agonist (209) . Thus, ZAG has emerged as a novel adipokine, being identified as an additional adipose tissue factor closely related to body weight loss not only via modulation of lipolysis in fat cells but also by activating AMPK in skeletal muscle cells (208,210) . The octapeptide angiotensin II (Ang II) is the active component of the renin-angiotensin system (RAS).…”
Section: Cytokines and Other 'Newcomers'mentioning
confidence: 99%
“…However, ZAG did not display the thermogenic effects of the b-adrenoceptor agonist, nor did it increase b 3 -adrenoceptor or UCP1 (uncoupling protein 1) gene expression in brown adipose tissue, thereby implying that it does not behave as a typical b 3/2 -adrenoceptor agonist (209) . Thus, ZAG has emerged as a novel adipokine, being identified as an additional adipose tissue factor closely related to body weight loss not only via modulation of lipolysis in fat cells but also by activating AMPK in skeletal muscle cells (208,210) . The octapeptide angiotensin II (Ang II) is the active component of the renin-angiotensin system (RAS).…”
Section: Cytokines and Other 'Newcomers'mentioning
confidence: 99%
“…Treatment with ZAG stimulates lipolysis in isolated mouse and human adipocytes, and it selectively reduces body fat in both with adiposity, triglycerides (TG), and the key components of metabolic syndrome (8). Additionally, ZAG expression and protein levels have been reported to be down-regulated in subcutaneous and visceral adipose tissue of obese men and women in comparison with the lean controls (9). Very recently, we have demonstrated that circulating ZAG levels are lower in the patients with impaired glucose tolerance (IGT) and patients with newly diagnosed type 2 diabetes mellitus (nT2DM) than in control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…ZAG promotes lipid metabolism through β-AR, stimulates uncoupler proteins in the mitochondria inner membrane to increase energy expenditure, increases number of skeletal muscle glucose transporters, stimulates AMP-activated protein kinase and acetyl-CoA carboxylase activity that promote fatty acid oxidation and glycerol release, and inhibits the activity of several key enzymes in the lipogenesis pathway 1, 4, 8, 12 . Due to its anti-obesity effects, ZAG is now considered a target for future therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that the introduction of ZAG producing tumors leads to up-regulation of ZAG in adipose tissue accompanied by profound WL due to fat depletion, without changing FFM or nutrient intake 1, 6 . ZAG knockout animals are more prone to weight gain than their wild-type siblings when given a high-fat diet 7, 8 . In addition, treatment with β-AR agonists stimulates ZAG production while β-AR antagonists suppress it, implying overexpression of ZAG is most likely regulated through β-AR and the sympathetic system in cachectic mice 3, 4 .…”
Section: Introductionmentioning
confidence: 99%